Psychometric Properties of the Psychological Needs Satisfaction Frustration Scale (BPNSFS) in Chilean University Students - Del Valle, Milenko (2018)
This research work aims to analyze the psychometric properties of the Basic Psychological Needs Satisfaction and Frustration Scale (BPNSFS) -autonomy, competence and relatedness- identified by the self-determination theory (Deci & Ryan, 2000b), in a sample of 297 university students from different faculties and programs belonging to a Chilean university. To achieve the objective, through a psychometric study by confirmatory procedures, a confirmatory factor analysis (CFA) was performed, analyzing the six-factor proposal developed by Chen et al. (2015), and the internal consistency of the scale was evaluated using the ordinal Alpha. The outcomes obtained from the sample of university students indicate a good internal consistency, Alpha = 0.90 and 0.86 for psychological needs satisfaction and frustration. Besides, the outcomes of the confirmatory factor analysis showed an adequate fit of the model (χ²/gl = 1.75; CFI = 0.92; IFI = 0.92; TLI = 0.90; RMSEA = .05 and SRMR =.05) to the data, showing evidences of the validity of the six-factor structure proposed. According to the foregoing, it is considered that the scale to measure satisfaction and frustration of the three basic psychological needs can be used initially in university students in the higher education of Chile, thus, allowing the relationship with other variables of interest to generate explanatory models that allow going in depth the understanding of aspects that are of institutional interest.